Method for preparing low-thermal-conductivity silicon mullite brick by utilizing basalt fiber and ceramic powder

By using basalt fibers and ceramic powder in the preparation process of low-thermal conductivity silicon mottle bricks, and adding additives such as theron powder and ammonium bicarbonate to form a stable network structure and pore structure, the existing low-thermal conductivity silicon mottle bricks are solved, and higher salinity and insulation properties are achieved.

CN119751074AActive Publication Date: 2025-04-04YIXING LONGCHANG REFRACTORIES CO LTD

Patent Information

Application Number
CN202411763527.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing low-thermal conductivity silicon mottle bricks have insufficient saline-alkali resistance, and the smooth surface and low surface area of ​​basalt fibers make it difficult to react with the matrix in polymer materials, affecting the performance of the composite materials.

Method used

Basalt fiber synergistic ceramic powder is used to form a stable network structure and pore structure by adding additives such as theron powder and ammonium bicarbonate to improve the salt-alkali resistance and thermal stability of the fibers. The thermal conductivity and mechanical strength of the material are optimized through the combination of the core-shell structure of the ceramic powder and the porous alumina material.

Benefits of technology

It significantly improves the saline-alkali resistance and thermal insulation properties of low-thermal conductivity silicon mottle bricks, reduces the thermal conductivity, enhances the thermal insulation effect, and improves the durability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168281450000081
    Figure BDA0005168281450000081
  • Figure BDA0005168281450000091
    Figure BDA0005168281450000091
Patent Text Reader

Abstract

The invention relates to the technical field of silicon mullite bricks, in particular to a method for preparing a low-thermal-conductivity silicon mullite brick by utilizing basalt fibers and ceramic powder. Comprising the following steps of S1, raw material preparation, S2, functional layer preparation, S3, thermal insulation layer preparation and S4, compression molding. The corrosion resistance and the thermal insulation performance of the low-thermal-conductivity silicon mullite brick are further optimized and improved through the synergistic effect of the basalt fibers and the ceramic powder, and the problem that the performance of a composite material is affected due to the fact that the basalt fibers are prone to being pulled out when stressed is solved. By adopting the ceramic powder with the core-shell structure, the mechanical property of the basalt fiber composite material can be remarkably improved, and the salt and alkali resistance and the heat preservation effect of the brick are optimized while the mechanical property of the low-heat-conductivity silicon mullite brick is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silica-molybdenum bricks, and in particular to a method for preparing low thermal conductivity silica-molybdenum bricks by utilizing basalt fibers and ceramic powder. Background Art

[0002] Basalt fiber (BF) is known as a pollution-free green industrial raw material. It is a continuous fiber made by rapidly drawing natural basalt under high temperature conditions. Its main chemical components are silicon dioxide, aluminum oxide, titanium dioxide and iron oxide. BF has the characteristics of chemical stability, mechanical properties, high temperature resistance, acid and alkali corrosion resistance and low cost. It is widely used as a reinforcing filler in polymer composite materials such as rubber and epoxy resin; low thermal conductivity refers to the low thermal conductivity of the material, that is, the material transfers less heat per unit area per unit time.

[0003] However, BF has a smooth surface, low surface energy, and small specific surface area. It is not easy to react with the polymer matrix and is easily extracted when subjected to force, which affects the performance of the composite material. In addition, the salt and alkali resistance of the low thermal conductivity silica-molybdenum bricks in the prior art is limited. In order to solve the above problems, the present invention decides to provide a method for preparing low thermal conductivity silica-molybdenum bricks using basalt fiber and ceramic powder. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder.

[0005] The technical solution of the present invention is: a method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder, comprising the following steps:

[0006] S1. Raw material preparation

[0007] Prepare the materials respectively using microporous mullite, silicon carbide powder, basalt fiber and ceramic powder as ceramic aggregates, agar powder as a molding agent, water as a solvent, ammonium bicarbonate as a pore-forming agent, pulp waste liquid as a binder, and Sialon powder and rigid polyurethane foam as additives;

[0008] The mass percentages of the components are as follows: 25-35% silicon carbide powder, 15-25% microporous mullite, 3-7% basalt fiber, 8-12% ceramic powder, 2-8% agar powder, 2-3% ammonium bicarbonate, 5-12% pulp waste liquid, 2-4% Sialon powder, 2-3% rigid polyurethane foam, and the balance is water; the ceramic powder is divided into 2-3 equal parts, and the pulp waste liquid is divided into 2-3 equal parts;

[0009] S2. Preparation of functional layer

[0010] Take one portion of the ceramic powder, and mix the silicon carbide powder, basalt fiber, agar powder and ammonium bicarbonate evenly to obtain a mixed powder, then add the Sialon powder into water and stir to prepare a mixed solvent, finally add the mixed solvent and one portion of the pulp waste liquid to the mixed powder in sequence and mix and grind for 10 to 15 minutes to obtain a functional layer;

[0011] S3. Preparation of thermal insulation layer

[0012] Take the microporous mullite, the remaining ceramic powder and the rigid polyurethane foam and mix them evenly, then pour in the remaining pulp waste liquid and mix and grind for 10 to 15 minutes to obtain the insulation layer mud, that is, the insulation layer;

[0013] S4, compression molding

[0014] The functional layer and the thermal insulation layer are pressed together to obtain a brick blank, which is naturally dried at 25-30°C for 20-24 hours, then dried at 100-130°C, and then fired at 1300-1450°C for 5-10 hours, and cooled to obtain the low thermal conductivity silica-molybdenum brick.

[0015] Description: Ammonium cyanide carbonate as a pore-forming agent can decompose and produce a large amount of gas during the sintering process, forming a uniform pore structure, improving the thermal insulation performance of the material, and at the same time can improve the compatibility of basalt fiber and ceramic powder, promote the combination between them, and enhance the internal structure of low thermal conductivity silica-molybdenum bricks. In addition, compared with other pore-forming agents, ammonium cyanide carbonate as a pore-forming agent has the ability to adjust the pH value of low thermal conductivity silica-molybdenum bricks, which can improve its salt and alkali resistance, enhance its durability in harsh environments, further improve the thermal conductivity of low thermal conductivity silica-molybdenum bricks, reduce its thermal conductivity coefficient, and improve the thermal insulation effect;

[0016] The Al and O elements in the Sialon powder can interact with the Si-O structure in the basalt fiber to form a more stable network structure, thereby improving the corrosion resistance of the fiber in salt solution. In salt solution, the Sialon powder can promote the formation of a protective compound film on the fiber surface, which can block the corrosion of salt ions on the fiber and reduce the loss of fiber performance; the high temperature stability of the Sialon powder can help the basalt fiber maintain its structural integrity in a high temperature environment, which is particularly important for resisting the corrosion of salt solutions at high temperatures; the Sialon powder can effectively promote the salt and alkali resistance of the basalt fiber by strengthening the fiber network structure, forming a protective layer, improving the pore structure and improving thermal stability; the rigid polyurethane foam has the effect of preventing the structure from collapsing at high temperatures, which can further improve the high temperature service life of the brick.

[0017] Furthermore, the length of the basalt fiber is 0.5 to 12 mm;

[0018] Note: When the fiber length is moderate, it can effectively reduce the connected pores and water seepage channels in cement concrete, form a spatial network structure, improve the density of concrete, and thus improve impermeability. However, if the fiber length is too long, it may be difficult to evenly distribute inside the concrete and keep it straight, resulting in more weak areas inside the concrete, and ultimately reducing impermeability. In addition, excessive and long fibers are not easy to disperse during the concrete mixing process, and may introduce too many bubbles, further reducing the density and impermeability of the concrete, thereby weakening the strength and durability of low thermal conductivity silica-molybdenum bricks.

[0019] Furthermore, the Sialon powder is Sialon powder doped with 0.5-2 wt.% of yttrium ions or ytterbium ions;

[0020] Note: Doping with yttrium or ytterbium ions can improve the thermal stability of Sialon powder, thereby enhancing the heat resistance of basalt fiber at high temperatures, which is beneficial to improving the service life of low thermal conductivity silica-molybdenum bricks; it can also optimize the crystal structure and micromorphology of Sialon powder, thereby improving the strength and toughness of basalt fiber and enhancing the tensile strength of low thermal conductivity silica-molybdenum bricks.

[0021] Furthermore, the ceramic powder is a core-shell structure, which is composed of a core, an intermediate layer, and an outer shell from the inside to the outside. The core is composed of a porous aluminum oxide material, the intermediate layer is composed of silicon nitride and aluminum nitride materials in an equal mass ratio, and the outer shell is composed of iron oxide and titanium oxide materials in an equal mass ratio.

[0022] Description: The iron element in basalt fiber exists in divalent and trivalent forms, among which trivalent iron (Fe 3+ ) content has a significant effect on the tensile strength of the fiber. 3+ / Σ(Fe 2+ +Fe 3+ ) ratio increases, crystals are easily precipitated in the fiber during the drawing process, which increases the defects on the fiber surface and thus reduces the tensile strength. The iron element in the outer shell layer can adjust the form and content of the iron element in the fiber through chemical reactions, which helps to optimize the network structure connection of the fiber and improve the tensile strength.

[0023] Furthermore, the diameter of the inner core is 15 to 55 nm, the thickness of the middle layer is 25 to 40 nm, and the thickness of the outer shell layer is 15 to 30 nm;

[0024] Note: The ceramic powder obtained at the above thickness not only has better thermal insulation effect, but can also effectively improve the service life of low thermal conductivity silica-molybdenum bricks in extreme environments such as high temperature, high pressure and highly corrosive media, thus broadening its application field.

[0025] Furthermore, the preparation method of the ceramic powder is:

[0026] S1: preparing a mixture for the outer shell layer: mixing iron oxide and titanium dioxide in a nitrogen atmosphere for 45 to 60 minutes to obtain a mixture for the outer shell layer;

[0027] S2: preparing an intermediate layer mixture: mixing silicon nitride and aluminum nitride materials in a nitrogen atmosphere for 45 to 60 minutes to obtain an intermediate layer mixture;

[0028] S3: preparing the inner core: taking 25-45wt% of macroporous alumina ceramic particles with a particle size of 100-150μm, 30-40wt% of mesoporous alumina ceramic particles with a particle size of 50-100μm and the remaining microporous alumina ceramic particles with a particle size of 10-50μm, mixing them to obtain an inner core mixture, loading them into a boron nitride crucible, and then moving them into a carbon tube furnace, first high-temperature calcining them under the protection of a nitrogen atmosphere, and then plasma ball milling them, and then introducing air at a rate of 5-10L / min for low-temperature calcining to form an inner core;

[0029] S4: preparing ceramic powder: under nitrogen protection, plasma spraying the intermediate layer mixture on the surface of the inner core, and then keeping the temperature at 900-1100° C. for 3-5 hours to obtain a ceramic semi-finished product, and then using vacuum plating to deposit the outer shell layer mixture on the surface of the ceramic semi-finished product, and keeping the temperature at 900-1100° C. for 3-5 hours to obtain ceramic powder;

[0030] Description: The ceramic powder prepared by the above method provides structural support and low thermal resistance channels through porous alumina, which is helpful for heat transfer. The silicon nitride and aluminum nitride materials in the middle layer effectively improve the overall thermal conductivity of the ceramic particles, and can also effectively balance the thermal expansion coefficient and mechanical strength of the material while maintaining a high thermal conductivity. The iron oxide and titanium dioxide materials in the outer shell layer help to optimize the network structure connection of the fiber and improve the tensile strength. The addition of titanium dioxide can reduce the viscosity of the basalt melt and promote Al 3+ Enter the network structure and enter the network structure in the form of TiO4 as a network precursor, thereby strengthening the polymerization and enhancing the impact resistance of the silica-molybdenum brick. In addition, the insoluble titanium hydroxide layer formed by TiO2 in the basalt fiber can reduce corrosion in the NaOH solution and improve the alkali resistance of the fiber; plasma ball milling treatment can increase the active sites of the solid phase reaction of the material, accelerate the mass transfer process, and improve the sintering activity, thereby obtaining a ceramic core with good thermal insulation performance at low temperature. High-temperature calcination followed by low-temperature calcination can optimize the rheological properties of the ceramic powder and improve the processability, thereby obtaining a ceramic powder with better thermal insulation performance.

[0031] Furthermore, in step S3, the temperature of the high temperature roasting is 1000-1200°C, the time of the high temperature roasting is 4-8h, and the atmosphere pressure of the high temperature roasting is 5-8Mpa; the temperature of the low temperature roasting is 300-350°C, the roasting time is 3h, and the atmosphere pressure of the low temperature roasting is 1-5MPa;

[0032] Description: Plasma ball milling can form a polymer layer on the surface of the powder, reduce the surface energy of the powder, reduce agglomeration, and thus improve the dispersibility of the ceramic powder. The ceramic powder treated under the above-mentioned high-temperature calcination parameters can promote the densification of the material and reduce the porosity, thereby improving the density and mechanical properties of the material, such as hardness and flexural strength. However, if the calcination temperature is too high, it may cause excessive grain growth, increase defects inside the material, and form a dense structure with fewer pores, which may reduce the thermal insulation performance and mechanical strength of the material; while low-temperature calcination parameters can promote the homogenization of the microstructure in the material, reduce defects, and further optimize the thermal insulation performance of the ceramic powder.

[0033] Further, in step S3, the plasma ball milling treatment parameters are: motor speed 500-800 r / min, discharge voltage 4-6 kV, discharge frequency 10-20 kHz, ball milling time 30-50 min, ball-to-material ratio 5-10:1;

[0034] Note: If the processing parameters of plasma ball milling are too large, it may cause excessive refinement of ceramic powder particles and restricted grain growth, thus affecting the density and thermal stability of the material. If the processing parameters of plasma ball milling are too small, it may not be sufficient to achieve effective material activation and microstructure optimization, which means that the ceramic powder particles are not refined enough and the grain growth is insufficient, resulting in insufficient density and thermal stability of the material.

[0035] Further, in step S4, the parameters of the plasma spraying are: working current 400-600A, arc voltage 50-75V, argon flow rate 20-50L / min, hydrogen flow rate 5-15L / min, powder feeding rate 2-5L / min, spraying distance 80-120mm, spraying angle 90°, argon as plasma gas and powder feeding gas, and hydrogen as combustion gas;

[0036] The parameters of the vacuum plating are: vacuum degree is 3×10 -3 ~5×10 -3 Pa, the preheating temperature is 70-150°C, the negative voltage applied to the target is 200-600V, and the deposition time is 10-20min;

[0037] Note: The deposition effect of the middle layer and the outer shell layer within the above parameter range is better, and the thermal insulation performance optimization effect of the ceramic powder is better.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention forms a more stable network structure by adding Sialon powder during the preparation of the functional layer and utilizing the interaction between the Al and O elements in the Sialon powder and the Si-O structure in the basalt fiber, thereby improving the corrosion resistance of the fiber in a salt solution. The present invention can also effectively promote the salt-alkali resistance of the basalt fiber by enhancing the fiber network structure, forming a protective layer, improving the pore structure, and improving the thermal stability.

[0040] (2) The present invention further optimizes and improves the corrosion resistance and thermal insulation performance of low thermal conductivity silica-molybdenum bricks through the synergistic effect of basalt fiber and ceramic powder. In view of the problem that basalt fiber has a smooth surface, low surface energy, small specific surface area, is not easy to react with the polymer material matrix, and is easily extracted when subjected to force, thus affecting the performance of the composite material, the use of ceramic powder with a core-shell structure can significantly improve the mechanical properties of basalt fiber composite materials. Specifically, the iron element in the outer shell layer can adjust the form and content of the iron element in the fiber through chemical reaction, which helps to optimize the network structure connection of the fiber and improve the tensile strength, thereby improving the mechanical properties of the low thermal conductivity silica-molybdenum bricks while optimizing their salt-alkali resistance and thermal insulation effect.

[0041] (3) The ceramic powder prepared by the present invention can provide certain structural support and low thermal resistance channels by using porous alumina as the core, which is conducive to heat transfer. The silicon nitride and aluminum nitride materials in the middle layer have high thermal conductivity and can effectively improve the overall thermal conductivity of the ceramic particles. The combination of silicon nitride and aluminum nitride in equal mass ratio as the middle layer can effectively balance the thermal expansion coefficient and mechanical strength of the material while maintaining high thermal conductivity. The iron oxide and titanium dioxide materials in the outer shell layer can provide additional protection and improve the service life of the ceramic powder. The iron element can adjust the form and content of the iron element in the fiber through chemical reaction, which is helpful to optimize the network structure connection of the fiber and improve the tensile strength. The addition of titanium dioxide can reduce the viscosity of the basalt melt and promote Al 3+ Into the network structure, and as a network precursor in the form of TiO4, enter the network structure, thereby strengthening the polymerization. In addition, the insoluble titanium hydroxide layer formed by TiO2 in the basalt fiber can reduce corrosion in NaOH solution and improve the alkali resistance of the fiber. DETAILED DESCRIPTION

[0042] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0043] Example 1: A method for preparing low thermal conductivity silica-molybdenum bricks using basalt fiber and ceramic powder, comprising the following steps:

[0044] S1. Raw material preparation

[0045] The ceramic aggregates are microporous mullite, silicon carbide powder, basalt fiber and ceramic powder, agar powder is used as a molding agent, water is used as a solvent, ammonium bicarbonate is used as a pore-forming agent, pulp waste liquid is used as a binder, and Sialon powder and rigid polyurethane foam are used as additives. The basalt fiber has a length of 5 mm. The Sialon powder is Sialon powder doped with 1.2 wt.% yttrium ions.

[0046] The mass percentage of each component is as follows: 30% silicon carbide powder, 20% microporous mullite, 5% basalt fiber, 10% ceramic powder, 5% agar powder, 2.5% ammonium bicarbonate, 9% pulp waste liquid, 3% Sialon powder, 2.5% rigid polyurethane foam, and the balance water; the ceramic powder is divided into 3 equal parts, and the pulp waste liquid is divided into 3 equal parts; the ceramic powder in this embodiment adopts a commercially available product;

[0047] S2. Preparation of functional layer

[0048] Take one portion of the ceramic powder, and mix silicon carbide powder, basalt fiber, agar powder and ammonium bicarbonate evenly to obtain a mixed powder, then add the Sialon powder into water and stir to prepare a mixed solvent, finally add the mixed solvent and one portion of the pulp waste liquid to the mixed powder in sequence and mix and grind for 13 minutes to obtain a functional layer;

[0049] S3. Preparation of thermal insulation layer

[0050] Take the microporous mullite, the remaining ceramic powder and the rigid polyurethane foam and mix them evenly, then pour the remaining pulp waste liquid into it and mix and grind for 13 minutes to obtain the insulation layer mud, that is, the insulation layer;

[0051] S4, compression molding

[0052] The functional layer and the thermal insulation layer are pressed together to obtain a brick blank, which is naturally dried at 28°C for 22 hours, then dried at 115°C, and then fired at 1350°C for 8 hours. The low thermal conductivity silica-molybdenum brick is obtained by cooling.

[0053] Embodiment 2: Different from Embodiment 1, the length of the basalt fiber is 0.5 mm.

[0054] Embodiment 3: Different from Embodiment 1, the length of the basalt fiber is 12 mm.

[0055] Example 4: Different from Example 1, the Sialon powder is Sialon powder doped with 0.5 wt.% yttrium ions.

[0056] Example 5: Different from Example 1, the Sialon powder is Sialon powder doped with 2 wt.% ytterbium ions.

[0057] Example 6: Different from Example 1, the mass percentage of each component is as follows: silicon carbide micropowder 25%, microporous mullite 15%, basalt fiber 3%, ceramic powder 8%, agar powder 2%, ammonium bicarbonate 2%, pulp waste liquid 5%, Sialon powder 2%, rigid polyurethane foam 2%, and water as the balance.

[0058] Example 7: Different from Example 1, the mass percentage of each component is as follows: silicon carbide micropowder 35%, microporous mullite 25%, basalt fiber 7%, ceramic powder 12%, agar powder 8%, ammonium bicarbonate 3%, pulp waste liquid 12%, Sialon powder 4%, rigid polyurethane foam 3%, and water as the balance.

[0059] Embodiment 8: Different from Embodiment 1, in step S4, natural drying is performed at 25°C for 20 hours, then drying is performed at 100°C, and then sintering is performed at 1300°C for 5 hours.

[0060] Example 9: Different from Example 1, in step S4, natural drying is performed at 30°C for 24 hours, then drying is performed at 130°C, and then sintering is performed at 1450°C for 10 hours.

[0061] Embodiment 10: Different from Embodiment 1, the ceramic powder is a core-shell structure, which is composed of a core, an intermediate layer, and an outer shell from the inside to the outside. The core is composed of a porous aluminum oxide material, the intermediate layer is composed of silicon nitride and aluminum nitride materials in a mass ratio of 1:1, and the outer shell is composed of iron oxide and titanium dioxide materials in a mass ratio of 1:1; the diameter of the core is 30nm, the thickness of the intermediate layer is 30nm, and the thickness of the outer shell is 22nm.

[0062] The preparation method of ceramic powder is as follows:

[0063] S1: preparing a mixture for the outer shell layer: mixing iron oxide and titanium dioxide in a nitrogen atmosphere for 52 minutes to obtain a mixture for the outer shell layer;

[0064] S2, preparing an intermediate layer mixture: mixing silicon nitride and aluminum nitride materials in a nitrogen atmosphere for 50 minutes to obtain an intermediate layer mixture;

[0065] S3: Preparation of inner core: 35wt% of macroporous alumina ceramic particles with a particle size of 100-150μm, 35wt% of mesoporous alumina ceramic particles with a particle size of 50-100μm and the remaining microporous alumina ceramic particles with a particle size of 10-50μm are mixed to obtain an inner core mixture, which is loaded into a boron nitride crucible, and then moved into a carbon tube furnace, and first high-temperature calcined under the protection of a nitrogen atmosphere with a pressure of 7Mpa, the high-temperature calcination temperature is 1100℃, the high-temperature calcination time is 6h, and then after plasma ball milling, air is introduced at a rate of 8L / min for low-temperature calcination, the low-temperature calcination temperature is 325℃, the calcination time is 3h, and the atmosphere pressure of the low-temperature calcination is 3MPa to form an inner core; wherein, the plasma ball milling treatment parameters are: motor speed 650r / min, discharge voltage 5kV, discharge frequency 15kHz, ball milling time 40min, ball-to-material ratio 8:1;

[0066] S4: preparing ceramic powder: under nitrogen protection, plasma spraying the intermediate layer mixture on the surface of the inner core, and then keeping the temperature at 1000°C for 4 hours to obtain a ceramic semi-finished product, and then vacuum plating the outer shell layer mixture on the surface of the ceramic semi-finished product, and keeping the temperature at 1000°C for 4 hours to obtain ceramic powder;

[0067] The parameters of plasma spraying are as follows: working current 500A, arc voltage 65V, argon flow rate 30L / min, hydrogen flow rate 10L / min, powder feeding rate 4L / min, spraying distance 80-120mm, spraying angle 90°, argon as plasma gas and powder feeding gas, hydrogen as combustion gas; the parameters of vacuum plating are as follows: vacuum degree 4×10 -3 Pa, the preheating temperature is 100 °C, the negative voltage applied to the target is 400 V, and the deposition time is 15 min.

[0068] Embodiment 11: Different from Embodiment 10, the diameter of the inner core is 15 nm, the thickness of the middle layer is 25 nm, and the thickness of the outer shell layer is 15 nm.

[0069] Embodiment 12: Different from Embodiment 10, the diameter of the inner core is 55 nm, the thickness of the middle layer is 40 nm, and the thickness of the outer shell layer is 30 nm.

[0070] Example 13: Different from Example 10, in S1, iron oxide and titanium dioxide are mixed in a nitrogen atmosphere for 45 minutes to obtain an outer shell layer mixture; in S2, silicon nitride and aluminum nitride materials are mixed in a nitrogen atmosphere for 45 minutes to obtain an intermediate layer mixture.

[0071] Example 14: Different from Example 10, in S1, iron oxide and titanium dioxide are mixed in a nitrogen atmosphere for 60 minutes to obtain an outer shell layer mixture; in S2, silicon nitride and aluminum nitride materials are mixed in a nitrogen atmosphere for 60 minutes to obtain an intermediate layer mixture.

[0072] Example 15: Different from Example 10, 25wt% of macroporous alumina ceramic particles with a particle size of 100-150μm, 30wt% of mesoporous alumina ceramic particles with a particle size of 50-100μm, and the remainder of microporous alumina ceramic particles with a particle size of 10-50μm are mixed to obtain a core mixture.

[0073] Example 16: Different from Example 10, 45wt% of macroporous alumina ceramic particles with a particle size of 100-150μm, 40wt% of mesoporous alumina ceramic particles with a particle size of 50-100μm and the remainder of microporous alumina ceramic particles with a particle size of 10-50μm are mixed to obtain a core mixture.

[0074] Example 17: Different from Example 10, high-temperature calcination is first carried out under the protection of a nitrogen atmosphere at a pressure of 5 MPa, the temperature of the high-temperature calcination is 1000°C, the time of the high-temperature calcination is 4 hours, and then after plasma ball milling treatment, air is introduced at a rate of 5 L / min for low-temperature calcination, the temperature of the low-temperature calcination is 300°C, the calcination time is 3 hours, and the atmosphere pressure of the low-temperature calcination is 1 MPa, to form an inner core.

[0075] Example 18: Different from Example 10, high-temperature calcination is first carried out under the protection of a nitrogen atmosphere at a pressure of 8 MPa, the temperature of the high-temperature calcination is 1200°C, the time of the high-temperature calcination is 8 hours, and then after plasma ball milling treatment, air is introduced at a rate of 10 L / min for low-temperature calcination, the temperature of the low-temperature calcination is 350°C, the calcination time is 3 hours, and the atmosphere pressure of the low-temperature calcination is 5 MPa, to form an inner core.

[0076] Example 19: Different from Example 10, the plasma ball milling processing parameters are: motor speed 500r / min, discharge voltage 4kV, discharge frequency 10kHz, ball milling time 30-50min, ball-to-material ratio 5:1.

[0077] Example 20: Different from Example 10, the plasma ball milling processing parameters are: motor speed 800r / min, discharge voltage 6kV, discharge frequency 20kHz, ball milling time 50min, ball-to-material ratio 10:1.

[0078] Example 21: Different from Example 10, the temperature is kept at 900°C for 3 hours to obtain a ceramic semi-finished product, and then the shell layer mixture is deposited on the surface of the ceramic semi-finished product by vacuum plating, and the temperature is kept at 900°C for 3 hours to obtain ceramic powder.

[0079] Example 22: Different from Example 10, the temperature is kept at 1100°C for 5 hours to obtain a ceramic semi-finished product, and then the shell layer mixture is deposited on the surface of the ceramic semi-finished product by vacuum plating, and the temperature is kept at 1100°C for 5 hours to obtain ceramic powder.

[0080] Example 23: Different from Example 10, the parameters of plasma spraying are: working current 400A, arc voltage 50V, argon flow rate 20L / min, hydrogen flow rate 5L / min, powder feeding rate 2L / min, and spraying distance 80mm.

[0081] Example 24: Different from Example 10, the parameters of plasma spraying are: working current 600A, arc voltage 75V, argon flow rate 50L / min, hydrogen flow rate 15L / min, powder feeding rate 5L / min, and spraying distance 120mm.

[0082] Embodiment 25: Different from Embodiment 10, the parameters of vacuum plating are: vacuum degree is 3×10 -3 Pa, the preheating temperature is 70 °C, the negative voltage applied to the target is 200 V, and the deposition time is 10 min.

[0083] Embodiment 26: Different from Embodiment 10, the parameters of vacuum plating are: vacuum degree is 5×10 -3 Pa, the preheating temperature is 150 °C, the negative voltage applied to the target is 600 V, and the deposition time is 20 min.

[0084] Experimental example: The description of this experimental example is based on the recorded schemes in Examples 1 to 26, and is intended to illustrate the practical application effect of the present invention.

[0085] In order to illustrate the performance of the low thermal conductivity silica-molybdenum bricks prepared by the present invention, the refractory bricks obtained in the embodiment and the comparative example were tested respectively, and the test method is as follows:

[0086] Salt and alkali resistance test method: The static crucible method is used to carry out the alkali corrosion resistance test. Samples with a size of 80mm×80mm×80mm are cut from each sample brick, and a cylindrical groove of φ36mm×40mm is drilled in the center to make a crucible. Then a 60mm×60mm×30mm thin plate is cut to make a crucible cover. The crucible and the crucible cover are dried, and 20g of pure chemical K2CO3 is loaded into each crucible. The crucible cover and the crucible are sealed with fire clay. The entire crucible is dried in an oven at 110℃ for 12h, then placed in an electric furnace and kept at 1100℃ for 5h. After natural cooling, the alkali corrosion resistance of the sample is evaluated by observing the appearance of the sample;

[0087] Thermal conductivity determination method: Determine at 800℃ according to the provisions of YB / T 4130;

[0088] Tensile strength determination method: Tested according to national standard JC / T 2197-2013;

[0089] 1. Investigate the influence of raw material composition on the performance of low thermal conductivity silica-molybdenum bricks

[0090] Blank group 1: Different from Example 1, only basalt fiber was added.

[0091] Blank group 2: Different from Example 1, only ceramic powder was added.

[0092] Comparative Example 1: Different from Example 1, the length of the basalt fiber is 15 mm.

[0093] Control Example 2: Different from Example 1, the Sialon powder in the raw material does not contain rare earth ions.

[0094] Table 1 Performance of low thermal conductivity silica-molybdenum bricks prepared in Examples 1 to 9, Blank Groups 1 to 2, and Comparative Examples 1 to 2

[0095] Grouping Thermal conductivity at 800℃W / mK Tensile Strength Alkali resistance Example 1 1.2 96 Level 1 Example 2 1.6 93 Level 1 Example 3 1.3 94 Level 1 Example 4 1.4 92 Level 1 Example 5 1.2 95 Level 1 Example 6 1.5 93 Level 1 Example 7 1.3 95 Level 1 Example 8 1.4 94 Level 1 Example 9 1.3 95 Level 1 Blank group 1 2.1 79 Level 1 Blank Group 2 1.7 83 Level 2 Comparative Example 1 1.9 87 Level 2 Comparative Example 2 1.8 85 Level 1

[0096] Conclusion: From the data comparison of Examples 1 to 3 and Control Example 1, it can be seen that as the length of basalt fiber increases, the thermal conductivity and tensile strength of the obtained low thermal conductivity silica-molybdenum bricks both show a trend of first increasing and then decreasing, which indicates that the overly long fibers are not easy to disperse during the concrete mixing process, and may introduce too many bubbles, further reducing the compactness and impermeability of the concrete, thereby weakening the strength and durability of the low thermal conductivity silica-molybdenum bricks. Taking all factors into consideration, the low thermal conductivity silica-molybdenum bricks reach the best under the conditions of Example 1; from the data comparison of Examples 1, Examples 4 to 5 and Control Example 2, it can be seen that the addition of rare earth ions can optimize the crystal structure and micromorphology of the Sialon powder, thereby improving the strength and toughness of the basalt fiber and enhancing the tensile strength of the low thermal conductivity silica-molybdenum bricks; from the comparison of Examples 1 to 9 and Blank Groups 1 to 2, it can be seen that the addition of basalt fiber and ceramic powder alone can indeed improve the alkali resistance and thermal insulation performance of the silica-molybdenum bricks, respectively, but the tensile effect is limited.

[0097] 2. Investigate the effect of ceramic powder preparation method on the performance of low thermal conductivity silica-molybdenum bricks

[0098] Table 2 Performance of low thermal conductivity silica-molybdenum bricks prepared in Example 1, Examples 10-26, and Comparative Examples 3-5

[0099]

[0100]

[0101] Comparative Example 3: Different from Example 10, the alumina ceramic particles are microporous alumina ceramic particles with a size of 10 to 50 μm.

[0102] Comparative Example 4: Different from Example 10, the titanium dioxide in the outer shell layer is replaced by phosphorus oxide.

[0103] Comparative Example 5: Different from Example 10, no plasma ball milling treatment is performed between the high-temperature calcination and the low-temperature calcination.

[0104] Conclusion: By comparing Example 1 and Examples 10 to 26, it can be seen that the ceramic powder prepared by the present method has a positive effect on improving the tensile strength of basalt fiber, while the commercially available ceramic powder used in Example 1 does not have the effect of improving the tensile strength of basalt fiber.

[0105] By comparing Example 10, Examples 15-16 and Control Example 3, it can be seen that the thermal insulation effect and tensile strength of the low thermal conductivity silica-molybdenum bricks obtained by using only microporous alumina ceramic particles in Control Example 3 are weakened. This is because the particle size of the alumina ceramic particles is limited to effectively reduce the thermal conductivity by using alumina particles with larger particle sizes, and use them to form larger pores in the microstructure. Air or gas is fixed in these pores, reducing the heat conduction path, thereby improving the thermal insulation performance, and large-size particles can form a stronger bond between particles at high temperatures, but too large a particle size may lead to stress. The force is concentrated, thereby improving the overall tensile resistance; mesoporous particles play a transitional role in thermal insulation performance. They maintain a certain porosity and do not significantly affect the structural strength of the material like macroporous particles. The reasonable distribution of mesoporous particles helps to improve the toughness of the material and improve the tensile resistance by optimizing the contact points between particles; the high density and small pores of microporous particles are conducive to forming a continuous thermal insulation layer, further improving the thermal insulation effect, and small-size particles can fill the gaps between large particles to form a denser structure, improve the overall strength and toughness of the material, and thus enhance the tensile resistance;

[0106] From the comparison of Example 10, Examples 13-14 and Comparative Example 4, it can be seen that the addition of phosphorus oxide can promote the formation of an alkali-resistant glass phase, reduce the corrosion of alkali metals, and enhance the alkali resistance of silica-molybdenum bricks, but it promotes grain growth at high temperatures, which may also weaken the tensile properties of the material, limiting the tensile resistance effect. The addition of titanium dioxide can reduce the viscosity of the basalt melt and promote Al 3+ Enter the network structure and enter the network structure in the form of TiO4 as a network precursor, thereby strengthening the polymerization and enhancing the tensile strength of the silica-molybdenum brick. In addition, the insoluble titanium hydroxide layer formed by TiO2 in the basalt fiber can reduce corrosion in NaOH solution and improve the alkali resistance of the fiber.

[0107] By comparing Example 10, Examples 17 to 18 and Control Example 5, it can be seen that if the plasma ball milling treatment is not performed in Control Example 5, the performance of the low thermal conductivity silica-molybdenum brick obtained will be greatly weakened. This shows that plasma ball milling can increase the active sites of the solid phase reaction of the material, accelerate the mass transfer process, and improve the sintering activity, thereby obtaining a ceramic core with good thermal insulation performance at a low temperature. High-temperature calcination followed by low-temperature calcination can optimize the rheological properties of the ceramic powder and improve the processability, thereby obtaining a ceramic powder with better thermal insulation performance.

Claims

1. A method for preparing low thermal conductivity silica-molybdenum bricks using basalt fiber and ceramic powder, characterized in that: The following steps are involved: S1. Raw material preparation Prepare the materials respectively using microporous mullite, silicon carbide powder, basalt fiber and ceramic powder as ceramic aggregates, agar powder as a molding agent, water as a solvent, ammonium bicarbonate as a pore-forming agent, pulp waste liquid as a binder, and Sialon powder and rigid polyurethane foam as additives; The mass percentages of the components are as follows: 25-35% silicon carbide powder, 15-25% microporous mullite, 3-7% basalt fiber, 8-12% ceramic powder, 2-8% agar powder, 2-3% ammonium bicarbonate, 5-12% pulp waste liquid, 2-4% Sialon powder, 2-3% rigid polyurethane foam, and the balance is water; the ceramic powder is divided into 2-3 equal parts, and the pulp waste liquid is divided into 2-3 equal parts; S2. Preparation of functional layer Take one portion of the ceramic powder, and mix the silicon carbide powder, basalt fiber, agar powder and ammonium bicarbonate evenly to obtain a mixed powder, then add the Sialon powder into water and stir to prepare a mixed solvent, finally add the mixed solvent and one portion of the pulp waste liquid to the mixed powder in sequence and mix and grind for 10 to 15 minutes to obtain a functional layer; S3. Preparation of thermal insulation layer Take the microporous mullite, the remaining ceramic powder and the rigid polyurethane foam and mix them evenly, then pour in the remaining pulp waste liquid and mix and grind for 10 to 15 minutes to obtain the insulation layer mud, that is, the insulation layer; S4, compression molding The functional layer and the thermal insulation layer are pressed together to obtain a brick blank, which is naturally dried at 25-30°C for 20-24 hours, then dried at 100-130°C, and then fired at 1300-1450°C for 5-10 hours, and cooled to obtain the low thermal conductivity silica-molybdenum brick.

2. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 1, characterized in that: The length of the basalt fiber is 0.5-12 mm.

3. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 1, characterized in that: The Sialon powder is Sialon powder doped with 0.5-2 wt.% of yttrium ions or ytterbium ions.

4. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 1, characterized in that: The ceramic powder is a core-shell structure, which consists of a core, a middle layer and an outer shell from the inside to the outside. The core is composed of a porous aluminum oxide material, the middle layer is composed of silicon nitride and aluminum nitride materials in an equal mass ratio, and the outer shell is composed of iron oxide and titanium dioxide materials in an equal mass ratio.

5. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 4, characterized in that: The diameter of the inner core is 15-55 nm, the thickness of the middle layer is 25-40 nm, and the thickness of the outer shell layer is 15-30 nm.

6. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 5, characterized in that: The preparation method of the ceramic powder is: S1: preparing a mixture for the outer shell layer: mixing iron oxide and titanium dioxide in a nitrogen atmosphere for 45 to 60 minutes to obtain a mixture for the outer shell layer; S2. preparing an intermediate layer mixture: mixing silicon nitride and aluminum nitride materials in a nitrogen atmosphere for 45 to 60 minutes to obtain an intermediate layer mixture; S3: preparing the inner core: taking 25-45wt% of macroporous alumina ceramic particles with a particle size of 100-150μm, 30-40wt% of mesoporous alumina ceramic particles with a particle size of 50-100μm and the remaining microporous alumina ceramic particles with a particle size of 10-50μm, mixing them to obtain an inner core mixture, loading them into a boron nitride crucible, and then moving them into a carbon tube furnace, first high-temperature calcining them under the protection of a nitrogen atmosphere, and then plasma ball milling them, and then introducing air at a rate of 5-10L / min for low-temperature calcining to form an inner core; S4: Preparation of ceramic powder: Under nitrogen protection, the middle layer mixture is plasma sprayed on the surface of the inner core, and then kept at 900-1100°C for 3-5 hours to obtain a ceramic semi-finished product, and then the outer shell layer mixture is deposited on the surface of the ceramic semi-finished product by vacuum plating, and kept at 900-1100°C for 3-5 hours to obtain ceramic powder.

7. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 6, characterized in that: In step S3, the high temperature roasting temperature is 1000-1200°C, the high temperature roasting time is 4-8h, and the high temperature roasting atmosphere pressure is 5-8Mpa; the low temperature roasting temperature is 300-350°C, the roasting time is 3h, and the low temperature roasting atmosphere pressure is 1-5MPa.

8. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 6, characterized in that: In step S3, the plasma ball milling processing parameters are: motor speed 500-800 r / min, discharge voltage 4-6 kV, discharge frequency 10-20 kHz, ball milling time 30-50 min, ball-to-material ratio 5-10:

1.

9. The method for preparing low thermal conductivity silica-molybdenum bricks by using basalt fiber and ceramic powder as claimed in claim 6, characterized in that: In step S4, the parameters of the plasma spraying are: working current 400-600A, arc voltage 50-75V, argon flow rate 20-50L / min, hydrogen flow rate 5-15L / min, powder feeding rate 2-5L / min, spraying distance 80-120mm, spraying angle 90°, argon as plasma gas and powder feeding gas, and hydrogen as combustion gas; The parameters of the vacuum plating are: vacuum degree is 3×10 -3 ~5×10 -3 Pa, the preheating temperature is 70-150°C, the negative voltage applied to the target is 200-600V, and the deposition time is 10-20min.

Citation Information

Patent Citations

  • Low-thermal conductivity silicon-mullite brick and preparation method thereof

    CN105924190A

  • Low aluminum silicon mullite brick for rotary cement kiln and preparation method thereof

    CN109111215A

  • Method for preparing high-strength porous composite ceramic from coal slime

    CN116444291A

  • Continuous carbon fiber reinforced ultra-high temperature ceramic matrix composite material and preparation method thereof

    CN116462525A

  • Crucible mold

    CN216472844U

Cited By

  • Liquid-liquid composite ceramic inlaid high-wear-resistance swinging hammer and preparation method thereof

    CN120551365A

  • Preparation process of low-thermal-conductivity and high-compactness refractory brick for molten salt storage tank

    CN121651993A